2014
DOI: 10.1080/02755947.2014.920740
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Variation of the Gill Rakers of Gizzard Shad and Silver Carp in Three Midwestern Rivers

Abstract: Improved management of invasive Silver Carp Hypophthalmichthys molitrix in the upper Mississippi River basin may be possible by better understanding the feeding abilities of this population. Food collection for filter‐feeding fishes, such as Silver Carp, is influenced by the species‐specific structure of their gill rakers. To investigate structural variation in gill rakers of Silver Carp, the morphology of gill rakers was quantified and compared with that of a native filter‐feeding fish species which may compe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…nobilis) throughout the Mississippi River basin has been documented by resource agencies since the 1970's (Kelly et al 2011). These prolific fish cause harm to native aquatic ecosystems by competing with native mussels, early life-stage fish, and other filter-feeding fish for food resources from a planktivorous diet overlap (Irons et al 2007;Sampson et al 2009;Walleser et al 2014). This increased competition has been demonstrated through major shifts in zooplankton communities on the Illinois River where silver and bighead carp are in high abundances (Sass et al 2014).…”
mentioning
confidence: 99%
“…nobilis) throughout the Mississippi River basin has been documented by resource agencies since the 1970's (Kelly et al 2011). These prolific fish cause harm to native aquatic ecosystems by competing with native mussels, early life-stage fish, and other filter-feeding fish for food resources from a planktivorous diet overlap (Irons et al 2007;Sampson et al 2009;Walleser et al 2014). This increased competition has been demonstrated through major shifts in zooplankton communities on the Illinois River where silver and bighead carp are in high abundances (Sass et al 2014).…”
mentioning
confidence: 99%
“…However, particles approaching 10 μm in size are within the range of particle sizes silver carp can consume (Smith, ), and their feeding can cause plankton communities to shift to smaller sizes, indicating that competition could still occur in a natural ecosystem. An established silver carp population would contain individuals across a variety of size classes, feeding on a range of particle sizes (Walleser et al, ), which could augment the adverse effects of silver carp on mussels. Further work to quantify feeding selectivity in both silver carp and mussels at varying sizes is necessary to understand fully the situations in which silver carp and mussels may overlap in diet.…”
Section: Discussionmentioning
confidence: 99%
“…Silver carp were introduced into the US as an algal control agent in aquaculture (Chick & Pegg, 2001). They are large-bodied and have been observed to consume zooplankton, phytoplankton and particles between 5 and 450 μm (Smith, 1989), although the sizes of particles consumed by silver carp may vary with total length owing to changes in the pore size of their gill rakers (Walleser, Sandheinrich, Howard, Gaikowski, & Amberg, 2014). Silver carp have spread to more than 80 countries worldwide (Kolar et al, 2007), possibly competing with native species throughout their invaded range (Gophen & Snovsky, 2015;Lübcker et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the ability to osmoregulate at different salinities was seen to increase throughout the developmental stages of the seabass (between larva and juvenile individuals) [45]. Additionally, body size was also identi ed as the main factor affecting morphological variation in gill rakes and the size of their pores in the Silver Carp and Gizzard Shad, suggesting that the overall ltering ability of these species is related to size and maturation [49]. Importantly, a recent study showed that increases in body weight are accompanied by increased microbial community structure of the skin and gill of rabbit sh [36].…”
Section: Microbial Diversity Across Age Groupsmentioning
confidence: 98%